2023
DOI: 10.3390/nu15133004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver X Receptors and Peroxisome Proliferator-Activated Receptors by Lipid Extracts of Brown Seaweeds: A Potential Application in Alzheimer’s Disease?

Nikita Martens,
Na Zhan,
Gardi Voortman
et al.

Abstract: The nuclear liver X receptors (LXRα/β) and peroxisome proliferator-activated receptors (PPARα/γ) are involved in the regulation of multiple biological processes, including lipid metabolism and inflammation. The activation of these receptors has been found to have neuroprotective effects, making them interesting therapeutic targets for neurodegenerative disorders such as Alzheimer’s Disease (AD). The Asian brown seaweed Sargassum fusiforme contains both LXR-activating (oxy)phytosterols and PPAR-activating fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 97 publications
2
6
0
Order By: Relevance
“…Because the cellular cholesterol content may affect the cytokine production of macrophages, we determined the effect of the extracts of H. elongata and S. fusiforme on cholesterol efflux in THP-1-derived macrophages [ 15 ]. In line with our previous findings that H. elongata and S. fusiforme extracts upregulate the expression of genes involved in cholesterol efflux [ 28 ], the H. elongata lipid extract and S. fusiforme SCF extract promoted the efflux of cholesterol from THP-1-derived macrophages. The H. elongata extract promoted the cholesterol efflux to ApoA-I and, to a lesser extent, to HDL, but only at a saringosterol concentration of 2.5 µM ( Figure 8 a,b).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Because the cellular cholesterol content may affect the cytokine production of macrophages, we determined the effect of the extracts of H. elongata and S. fusiforme on cholesterol efflux in THP-1-derived macrophages [ 15 ]. In line with our previous findings that H. elongata and S. fusiforme extracts upregulate the expression of genes involved in cholesterol efflux [ 28 ], the H. elongata lipid extract and S. fusiforme SCF extract promoted the efflux of cholesterol from THP-1-derived macrophages. The H. elongata extract promoted the cholesterol efflux to ApoA-I and, to a lesser extent, to HDL, but only at a saringosterol concentration of 2.5 µM ( Figure 8 a,b).…”
Section: Resultssupporting
confidence: 92%
“…We first tested whether S. fusiforme SCF extract activated LXRs, as previously demonstrated with the chloroform–methanol extracts of S. fusiforme and H. elongata [ 25 , 28 ], using a cell-based dual luciferase reporter assay. The data demonstrated that the S. fusiforme SCF extract activated both LXRα and LXRβ in HEK293, CCF-STTG1, SH-SY5Y, and CHME3 cells ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A disturbed brain C metabolism is associated with Alzheimer’s disease (AD) and stimulation of cholesterol turnover in the brain was found to ameliorate the development of cognitive decline in AD mice. Martens et al [ 20 ] described the upregulation of C efflux genes and downregulation of lipogenesis genes by incubation with lipophilic extracts of six European brown seaweed species. Their results confirm the described prevention of disease progression in AD mice by the Asian brown seaweed species Sargassum fusiforme [ 21 ].…”
mentioning
confidence: 99%